Spatio-Temporal Dynamics of Sediment Transport Pathways: Sand Apron Bars and Islands of Tokelau and Kiribati, Central Pacific - Eugene C. Rankey; Tion Uriam; Mika Perez (Earth Science, Systems and Society)
Although there is general agreement that global change will influence low-lying atoll islands, considerable uncertainty remains concerning the nature, rates, and causes of morphological change (or, conversely, the stability) of islands. As the net geomorphical product of sediment erosion, transport, and accumulation, islands are intimately tied to reef flat sedimentological processes. Recognizing the morphodynamical linkages between reef flats and islands, the purpose of this study is to examine the nature and controls on spatial and temporal variations in sediment transport pathways on reef flats and their relation to island planform changes or stability on atolls of Tokelau and Kiribati. GIS analysis of historical aerial images and high-resolution remote-sensing data capture patterns of reef flat change up to 72 years in duration with up to weekly temporal resolution. Data reveal how granular materials that make up bars and islands on reef flats respond to physical oceanographic processes via sedimentary-geomorphical change across temporal scales, from “instantaneous” impacts of cyclones or swell events to seasonal to multi-decadal shifts. Each of these shifts is manifest as migration of sediment of island beaches and bar forms, but the character varies markedly—bars form new islands, others erode and disappear; some changes are cyclic, others are directional, still others are hybrid; sediment can be transported lagoonward, oceanward, along the reef flat, or in combinations thereof; and migration rates reach up to 10 s of m/month. Although sea-level change likely plays a modulating role, much of the considerable spatial and temporal variability relates to differences in energy controlled by seasonal change in swell direction and climate shifts. Nonetheless, sedimentary response to these external forcings at any specific location also is shaped by local factors, such as trade wind-generated lagoonal waves and currents, atoll lagoon size and depth, margin width and orientation relative to waves, and autogenic processes such as attachment of migrating bars. Collectively, these influences shape the spatially and temporally heterogeneous sediment flux to and from islands, and thus the variable response of islands to ongoing sea-level change. Understanding such local influences is requisite to predictive understanding of how global change might impact these sensitive seascapes.